Association between behavioural risk factors for hypertension and concordance with the Dietary Approaches to Stop Hypertension dietary pattern among South Asians in the Mediators of Atherosclerosis in South Asians Living in America (MASALA) study - Bridget Murphy Hussain; Andrea L. Deierlein; Alka M. Kanaya; Sameera A. Talegawkar; Joyce A. O’Connor; Meghana D. Gadgil; Belinda L. Needham; Yong Lin; Niyati Parekh (Journal of Nutritional Science)
South Asians are among the fastest-growing immigrant population group in the United States (U.S.) with a unique disease risk profile. Due in part to immigration and acculturation factors, South Asians engage differently with behavioural risk factors (e.g. smoking, alcohol intake, physical activity, sedentary behaviour, and diet) for hypertension, which may be modified for the primary prevention of cardiovascular disease. Using data from the Mediators of Atherosclerosis in South Asians Living in America cohort, we conducted a cross-sectional analysis to evaluate the association between behavioural risk factors for cardiovascular disease and diet. We created a behavioural risk factor score based on smoking status, alcohol consumption, physical activity, and TV watching. We also calculated a Dietary Approaches to Stop Hypertension (DASH) dietary score based on inclusion of relevant dietary components. We used both scores to examine the association between engaging with risk factors for hypertension and the DASH diet among a cohort of South Asian adults. We found that participants with 3–4 behavioural risk factors had a DASH diet score that was 3 units lower than those with no behavioural risk factors (aβ: –3.25; 95% CI: –4.28, –2.21) and were 86% less likely to have a DASH diet score in the highest category compared to the lowest DASH diet score category (aOR: 0.14; 95% CI: 0.05, 0.37) in the fully adjusted models. These findings highlight the relationship between behavioural risk factors for hypertension among South Asians in the U.S.